ANALISIS PENERAPAN MEDIA POWTOON DALAM MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - Hafidz Agung Setyawan; Deni Adi Putra; Fajar Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of Powtoon media in elementary school mathematics learning and to explore students' experiences when using the media. A qualitative descriptive approach was employed, with data collected through interviews and observations. The findings reveal that the use of Powtoon in mathematics lessons positively influences students' learning interest and comprehension.The engaging visualizations and animations presented through Powtoon successfully capture students’ attention, create a more enjoyable learning atmosphere, and help them grasp mathematical concepts more concretely. Furthermore, Powtoon encourages active student participation during the learning process. This media has proven to be a creative alternative that enhances the effectiveness of mathematics instruction, particularly in teaching arithmetic at the elementary school level.